DEFORMING THE ELASTIC CYLINDER WITH RING FIBERS UNDER THE ACTION OF ROTATION AT THE HARD SITTING - Kostrova, M. M. (Computer Science and Applied Mathematics, 2017)
We represent the results of the solution of the problem of deformation of a body about their axis of symmetry. Fibers of square cross-section are located in the matrix. The cylinder was modeled as an assembly of annular elements. Ring elements are presented in the form of rings of square cross-section from the matrix material, including ring fibers of square cross-section as their reinforcing core. The axisymmetric deformation corresponding to macroscopically flat deformation was studied when the length of the cylinder remained unchanged. Because of the symmetry conditions, the problem was solved for a half disk layer. Such a layer is enclosed between the cross sections of the cylinder, one of which passes through the axial lines of the fibers, and the other passes through the matrix between the fibers, with a distance between sections equal to half the reinforcement period along the axial direction. A distinctive feature for moving cylinders of elastic components is the effect on centrifugal forces affecting the matrix and fiber, changes in the distances from their material points to the axis of the cylinder. We used a model of a piecewise homogeneous medium, which methodologically most accurately reflects the behavior of the body of a fibrous structure. Exodus from geometric, physical equations and equilibrium equations of the nonlinear mechanics of the deformable body of the body. The relationship between physical and physical processes. This system of equations was solved on the basis of the Newton discrete method. The uniqueness of the solution of the boundary value problem was ensured on the basis of the continuation of the solution with respect to the angular velocity of rotation of the cylinder.